ORGANIZATIONAL CULTURE AND WORK SATISFACTION IN RELATION TO THE EMPLOYEE’S WORK BY PT. PEMBANGUNAN JAYA ANCOL - Rosa, Rosa Agustina Nababan; Christina N.Sihombing; L.Toruan, Rutman (Buletin Ekonomi, 2024)
The purpose of this research is to understand how the relevance of organizational culture and satisfaction in work on the performance produced by employees at PT Pembangunan Jaya Ancol. The nature of this study is quantitative while the use of data is through distributing questionnaires to respondents, totaling 53 employees as a sample, then utilizing secondary data by looking at company profiles, as well as supporting journals. in the analysis the Non-parametric statistics are used. according to the SPSS 24 software while the hypothesis aims to be able to see the relevance of the variables that refer to spearmen's rank correlation analysis and the t test. The determination of the value of 0.000 is so small compared to 0.05 this indicates a rejection of H0. Then there is acceptance of Ha which indicates the great relevance of culture within the organization to support the level of performance produced by employees. based on the organizational culture correlation value of 0.774, this means that the correlation is positive. This indicates that the culture in the organization is so high or these conditions make